Aristolochia sanheensis (Aristolochiaceae), a new species from Yunnan, Southwest China - Yang, Jian-Mei; Huang, Rui-Zhou; Liu, Jia-Zhu; Zhang, Chao-Jiang; Yang, Yu-Rong; Yin, Lun (Phytotaxa, 2024)
Aristolochia sanheensis, a new species from Yunnan, Southwest China, is described and illustrated for the first time. It is similar to A. luudamcui from northern Vietnam in the morphology of the calyx shape and the color of the inner calyx tube and limb, but is clearly distinguished by the limb triangular in lateral view, the prickly outgrowths of the inner limb, and the upper part of limb separated to ca. 1/2–2/3. It is evaluated as Critically Endangered (CR) according to the IUCN categories and criteria.